MNGI-41. LARGE VOLUME RE-IRRADIATION FOR RECURRENT MENINGIOMA WITH PULSED REDUCED DOSE RATE RADIOTHERAPY. (5th November 2018) - Witt, Jacob; Musunuru, Hima; Bayliss, Adam; Howard, Steven
Abstract: BACKGROUND: Meningiomas comprise up to 30% of primary brain tumors. The majority of meningioma patients enjoy high rates of control after conventional therapies. However, patients with recurrent disease previously treated with radiotherapy have few options for salvage treatment, and systemic interventions have proven largely ineffective. The aim of this study was to determine whether PRDR radiotherapy was well tolerated and effective in patients with recurrent meningioma. METHODS: We retrospectively identified 8 patients with recurrent intracranial meningioma treated with PRDR from April 2013 to August of 2017 at a single institution. All patients had radiographic and/or pathologic evidence of progression prior to treatment and had previously completed conventional radiotherapy. Relevant patient, tumor, and treatment characteristics were abstracted from the electronic medical record. Acute and late toxicities were graded based on CTCAE 4.0. RESULTS: Of 8 patients, 6 had histologically confirmed atypical meningiomas upon recurrence. All patients were re-treated with IMRT at an apparent dose rate of 0.0667 Gy/min. Median time between radiation courses was 7.7 years. Median PRDR dose was 54 Gy in 27 fractions to a median volume of 261.6 cm 3 . Two patients (25%) had in field failure with a median follow up of 23.3 months. PFS at 6 months was 100%. All but one (87.5%) patient was still alive at last follow up. No patient experienced grade ≥2 acute or late toxicities. CONCLUSION: PRDR re-irradiation is a viable option for patients with recurrent meningioma previously treated with radiotherapy. A phase II trial to assess this prospectively is in development.